An efficient interactive framework for improving resilience of power-water distribution systems with multiple privately-owned microgrids - Najafi, Javad; Peiravi, Ali; Anvari-Moghaddam, Amjad; Guerrero, Josep.M. (International journal of electrical power & energy systems, 2020)
•Microgrids with private owners can enhance the resilience of integrated PDN and WDN.•Water consumption pattern and damages of WDN can affect the restoration of loads.•Impact of DR on resilience improvement is investigated with a new proposed index. Resilience improvement of power distribution networks against natural disasters is an important problem. Water network similar to other important infrastructures depends on power networks. In this paper, resilience improvement is defined as increasing the users’ accessibility to water and power after natural disasters. Microgrids with appropriate operation can provide energy to restore disconnected loads in distribution networks. In the proposed interactive framework, a stochastic energy management program for microgrids is designed that not only determines the amount of energy can be delivered to distribution systems, but also considers the reliability of local loads during emergency conditions. Each microgrid provides a list of bid-quantity energy blocks to the distribution system operator (DSO) during the emergency period. Then, the DSO chooses the best plan to restore disconnected loads considering inaccessibility values to power and water and also the damage of power and water distribution networks. Demand response actions in microgrids are also considered as effective tools for the energy management program, and their impact on the distribution system resilience is investigated. The proposed model is tested on the modified IEEE 33-bus distribution system with multiple microgrids, and the effectiveness of the proposed method is validated accordingly.